Changes in dive patterns of leatherback turtles with sea surface temperature and potential foraging habitats - Okuyama, Junichi; Benson, Scott R.; Dutton, Peter H.; Seminoff, Jeffrey A. (Ecosphere (Washington, D.C), 2021)
Marine mesotherms are able to occupy broader thermal niches than ectotherms; however, this means they must thermoregulate according to diverse thermal conditions across the ocean. Knowledge remains limited about how differences in thermal conditions within the selected habitats affect the behavior and associated ecological traits in mesotherms. Here, we tested if a marine mesotherm, leatherback turtles (Dermochelys coriacea) generally maintain their body temperature by diving to greater depths to expose themselves to cold waters as sea surface temperature becomes warmer. Moreover, we investigate how such behavioral thermoregulation may influence their ecological traits (e.g., foraging and migration). We analyzed 49,461 dive profiles and 16,255 temperature‐depth profiles from 17 leatherback turtles migrating across the North Pacific using satellite‐linked data loggers. Our results showed that leatherbacks changed their dive behavior regionally, in response to sea surface temperature and potential foraging habitats. Dive type classification revealed that V‐shaped, presumably gliding dives, became deeper when the surface water was warmer, likely because leatherbacks dive to deep cold waters to avoid overheating. We found five hotspots of wiggle (up‐and‐down undulations in the depth profile) dives that are indicative of foraging behavior, ranging from tropical to cool‐temperate regions in the North Pacific. The dive patterns in potential foraging hotspots indicate that leatherbacks engage in behavioral thermoregulation in warmer regions. Such bioenergetics may affect the time available for foraging activity during migration phases. In cool‐temperate foraging areas, leatherbacks are indeed able to spend more time foraging due to mesothermy. However, the trade‐off between energy gain by foraging activity and additional migration cost of moving to higher latitude areas might not result in greater reproductive output for leatherbacks foraging in distant cool‐temperate regions. These patterns highlight that mesothermy represents a trade‐off: Leatherbacks can utilize cooler waters but must engage in additional behavioral thermoregulation (i.e., extremely deep dives) in warmer waters. Thus, mesothermy might not provide a direct fitness advantage to all individual leatherback turtles; rather, it affords a species‐level fitness advantage by allowing a greater diversity of habitats to be utilized.